Dehydrogenative synthesis of benzimidazoles under mild conditions with supported iridium catalysts. Issue 6 (21st October 2015) - Tateyama, Keisuke; Wada, Kenji; Miura, Hiroki; Hosokawa, Saburo; Abe, Ryu; Inoue, Masashi
Abstract : Recyclable Ir/TiO2 catalysts enable the synthesis of benzimidazoles from primary alcohols and phenylenediamines under mild conditions, i.e. at 120 °C. Abstract : Solid supported iridium catalysts, which show excellent activity for the dehydrogenative synthesis of benzimidazoles from primary alcohols and phenylenediamine derivatives under mild reaction conditions, were developed. Among the catalysts examined, the titania-supported iridium catalyst showed the highest activity, and benzimidazole derivatives were selectively produced at temperatures of 80 °C or higher. For example, the reaction of phenylenediamine (1a ) with benzyl alcohol (2a ) in the presence of Ir(1.0 wt%)/TiO2 (1.0 mol%, towards1a ) at 120 °C selectively gave 2-phenylbenzimidazole (3aa ) in 80% yield after 6 h and over 90% yield after 18 h. A high turnover number (TON) of more than 800 was achieved in the reaction at a higher substrate-to-catalyst ratio. Reduction of the catalysts under a hydrogen atmosphere at around 500 to 600 °C is essential for their significant activity. Characterization of the catalysts by gas adsorption, XRD, XPS, H2 -TPR, TEM, and XAFS techniques revealed that highly-dispersed nanoparticles of the iridium(0) species ( ca. 1 to 2 nm in diameter) formed on TiO2 are responsible for the catalysis. The catalysts could be recycled without a significant loss of activity, and the leaching of the iridium species into the solution during the catalytic runs was negligible, which suggests that the present catalysts would be excellent from both environmental and practical perspectives.